Growth GROWTH DESCRIPTION (BB/U, TB/U, BB/TB) CHILDREN AGE 4-5 YEARS (In Endah Kinder Garden Bandar Lor Subdistrict Mojoroto, Kediri City) - Aida Ratna Wijayanti; Siti Komariyah (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2019)
Growth (growth) is a quantitative change, which is increasing the number, size, dimensions at the level of cells, organs, and individuals, one of the important factors that influence child development is nutritional factors. The root of the nutritional problem is the economic, political and social crisis in society, causing food shortages, poverty and high rates of inflation and unemployment. This study aims to determine the growth picture (BB / U, TB / U, BB / TB) of children aged 4-5 years at Kindergarten Endah Bandar Lor, Mojoroto District, Kediri City. The design of this research is descriptive with cross sectional approach. The population of all children aged 4-5 years at Kindergarten Endah Bandar Lor, Mojoroto District, Kediri City. The sampling technique used was Total Sampling, so a sample of 28 children was obtained. The research variable is the growth of children aged 4-5 years. data collection using observation sheets, measuring height and weight. Data processing by editing, coding, scoring, tabulating. Data were analyzed using percentages. This research was conducted on 28 respondents with the results of Height / Age 25 respondents in the normal category, Weight / Age 21 respondents in the category of good nutrition, Weight / Height 20 respondents in the Normal category It is expected that health workers are more active in providing counseling about child development to the community. From the results of this study it can be concluded that the growth of children aged 4-5 years old at TK Endah Bandar Lor is normal. It is expected that health workers will collaborate with the school and parents for monitoring and stimulating children's growth.